Questioning leadership a framework für growth and purpose - Harvey, Michael 1960- (Cambridge elements. Elements in Leadership, 2024)
This Element posits that questions are the heart of leadership. Leaders ask hard questions that spark creative solutions and new understandings. Asking by itself isn't enough - leaders must also help find answers and turn them into effective action. But the leader's work begins with questions. This Element surveys the main traditions of leadership thought; considers the nature of the group and its questions; explores how culture and bureaucracy serve to provide stable answers to the group's questions; and explores how leaders offers disruptive answers, especially in times of change and crisis. It uses the lens of questions to consider two parallel American lives, President Abraham Lincoln and General Robert E. Lee